Agent-Based Fire Evacuation Model as a Tool for Fire Safety Design Assessment in Malaysia - Yi Rong, Tan; Akashah, Farid; Mahyuddin, Norhayati (International Journal of Property Sciences (E-ISSN: 2229-8568), 2014)
Evacuation model is an important tool in formulating performance-based building design. It is a tool aims at helping designers assess the robustness of their design against factors such as human behaviour in fire. Currently, performance-based code for fire safety design has been the hot trend all over the world. Nevertheless, even though Malaysia is applying prescriptive-based code, performance-based approach for special buildings and mega projects are allowed. This shows that it is just a matter of time before performance-based code be fully adopted in place of prescriptive-based code in Malaysia. This paper aims to highlight how evacuation modelling may help designers assess the performance of their design. In this paper, an example of evacuation scenario was modelled and simulated using an agent-based fire evacuation model – FDS+Evac. The output of the simulation provide graphical representation such as the fire curve, the evacuation time, and the time to untenable condition that can be used to analyse the life safety objective based on concepts of ASET and RSET. The FED values of all occupants throughout the evacuation process are less than tenability criteria (0.3 FED). Therefore, it is concluded that all occupants have evacuated safely in the event of fire.